A Bartha József vezette üzleti körök szerepe a magyar kereskedelmi tengerészet történetében (1929–1949). - Pelles, Márton (Közép-Európai Közlemények, 2024)
The golden age of the development of the Hungarian merchant marine was interrupted by the Trianon peace decree that ended the First World War. In landlocked Hungary, many former sailors and ship owners were left without livelihood and property due to the merchant fleet taken away due to war reparations. Jenő Polnay first tried to solve the crisis that arose, but his activities between 1921 and 1929 were unsuccessful. In 1929, however, a new organizer appeared on the scene: József Bartha, a Hungarian shipowner from Trieste, who, through his extensive business connections could take an advantage of the discounts provided by the Hungarian state, founded a number of shipping companies in the 1930s. In our study, we present how József Bartha was able to unite groups of international ship owners, Hungarian sailors, professionals and investors in a wide variety of relationships, and how he brought the Pannónia Hungarian Shipping Co., the Hungarian Overseas Shipping Company, the Hungarian Orient-Line Shipping Company, and the Merchant Shipping Company. Our research is the first to write the history of these companies, using the wide range of Hungarian archives, relevant literature, daily press materials and statistical sources.